On the Convergence of the Homotopy Analysis Method for Inner-Resonance of Tangent Nonlinear Cushioning Packaging System with Critical Components - Mohammad Ghoreishi; A. I. B. Md. Ismail; Abdur Rashid (Abstract and Applied Analysis)
Homotopy analysis method (HAM) is applied to obtain the approximate solution of inner-resonance of tangent cushioning packaging system based on critical components. The solution is obtained in the form of infinite series with components which can be easily calculated. Using a convergence-control parameter, the HAM utilizes a simple method to adjust and control the convergence region of the infinite series solution. The obtained results show that the HAM is a very accurate technique to obtain the approximate solution.